Perjanjian Pranikah untuk Tidak Selingkuh Perspektif Hukum Islam di Indonesia - Fadillah, Rahmat Fadillah; Subehi, M. Beta (PT. Sharia Journal and Education Center, 2024)
The more advanced human civilization becomes, the more problems occur among humanity. One of the problems that arise is related to relationships between people. Trust issues are a hot topic being discussed nowadays, including in husband-wife relationships. Trust issues influence prospective husbands or wives to enter into prenuptial agreements. The contents of the agreement are about the prohibition of cheating, as was done by artist Via Vallen and her husband Chevra Yolandi. They made this agreement so that each of them would think again about committing cheating because there were consequences if they broke the agreement. Not without reason, quite a few cases of infidelity have occurred between ordinary people and public figures in the country. The purpose of this research is to find out how Islamic law views prenuptial agreements which include a prohibition on cheating in them? This research uses a type of normative juridical research with library research. The research results show that marriage should be carried out based on mutual trust in each partner.